Effect of Integrated Nutrient Management on Tuber Dry Matter Accumulation and Uptake of Nutrients by Potato (Solanum Tuberosum L.) (Global Journal of Science Frontier Research, 2023)
Potatoes have received a reputation as being a large consumer of nutrients such as nitrogen (N), phosphorus (P) and potassium (K). An experiment was conducted to study the effect of integrated nutrient management on the dry matter accumulation and uptake of nutrients in potato (Solanum tuberosum L.). Application of 50% RDF + 50% FYM + Azotobacter + Phosphobacteria (T7) recorded maximum total dry matter production (21.67%) which was on per with T3 (20.53%) and followed by T4 (19.79%), T5 (19.19%), T9 (18.55%) and T6 (18.42) during rabi 2011. Similarly the maximum uptake of N (97.17 kg/ha), P (21.76 kg/ha) and K (159.63 kg/ha) was found with plants provided with 50%RDF + 50%FYM + Azotobacter + PSB (T7) which was on par with T4, T3 and T5 during rabi 2011.
Keywords: potato; azotobacter; phosphobacteria; dry matter production; nutrient uptake; NPK concentration and vermicompost